2020
DOI: 10.12669/pjms.36.4.1845
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated epidermal growth factor and tumor growth factor-beta receptor signaling through GFAP-ACTA2 protein interaction in liver fibrosis

Abstract: Objective: Viral hepatitis is associated with high morbidity and mortality. Identification of biological pathways involved in hepatic fibrosis resulting from chronic hepatitis C are essential for better management of patients. Constructing the HCV-human protein interaction network through bioinformatics may enable us to discover diagnostic biological pathways. We investigated to identify dysregulated pathways and gene enrichment based on actin alpha 2 (ACTA2) and glial fibrillar acidic protein (GFAP) interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…What is more, the ACTA2 has been indicated to be associated with hepatitis C virus-induced hepatic fibrosis. 38 Here, we also reported an upregulated expression level of ACTA2, which is consistent with a previous study. However, due to the relatively small number of clinical samples available in this study, and the complex mechanism of liver cirrhosis, further studies and large sample studies, incorporating clinical information, are required to validate the functions of these genes in liver cirrhosis or HCC progress.…”
Section: Discussionsupporting
confidence: 93%
“…What is more, the ACTA2 has been indicated to be associated with hepatitis C virus-induced hepatic fibrosis. 38 Here, we also reported an upregulated expression level of ACTA2, which is consistent with a previous study. However, due to the relatively small number of clinical samples available in this study, and the complex mechanism of liver cirrhosis, further studies and large sample studies, incorporating clinical information, are required to validate the functions of these genes in liver cirrhosis or HCC progress.…”
Section: Discussionsupporting
confidence: 93%
“…[30,31] PRKCA has also been reported to be involved in the brosis process of liver, kidney and other organs. [16,17] Our results showed that PRKCA is the target gene of miR-647, participate in miR-647 regulated process of atrial brosis, indicating that PRKCA is an important gene in the pathogenesis of AF.…”
Section: Discussionmentioning
confidence: 65%
“…Recent researches discovered that up-regulation of PRKCA could increase the brosis of renal and liver. [16,17] Additionally, PRKCA increases the vulnerability to AF by dysregulation of calcium signaling, suggesting that PRKCA may be involved in the occurrence and maintenance of AF. [18] In our previous studies, bioinformatics analysis was used to analyze the differentially expressed genes in atrial tissues of sinus rate (SR) and AF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of HSCs and their transformation to myofibroblasts is an example of that one. Moreover, another example of cell transformation caused by TGF-β is EMT in hepatocytes accompanied with loss of cell-cell contacts and polarity [50]. Actually, TGF-β stimulates almost of all liver cell populations (portal and resident fibroblasts, bone marrow-derived fibrocytes, endothelial cells, vascular smooth muscle cells, pericytes and cholangiocytes additionally to hepatocytes and HSCs) to change into a more fibroblastic phenotype [40] and to release profibrogenic transcriptional program manifested by upregulation of collagen expression [41] and disturbances in ECM turnover through imbalance between MMPs and TIMPs.…”
Section: Tgfβrmentioning
confidence: 99%